1996
DOI: 10.1097/00002060-199601000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Functional Electrical Stimulation-Induced Lower Extremity Cycling on Bone Density of Spinal Cord-Injured Patients1

Abstract: Spinal cord-injured (SCI) patients are at increased risk for fractures secondary to neurogenic osteoporosis. Earlier research claimed physical conditioning resulted in a decreased incidence or reversal of neurogenic osteoporosis. This study evaluated the effects of functional electrical stimulation-induced lower extremity cycling (FESILEC) on the bone densities of SCI patients using dual-energy x/ray absorptiometry (DEXA). The study consisted of 12 healthy male SCI patients, aged 23 to 46 (x +/- SD, 34 +/- 6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0
6

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 21 publications
3
77
0
6
Order By: Relevance
“…Hip region BMD in our SCI group was 67, 66 and 63% that of the control group, for FN, WT and T, respectively. These ®gures are slightly lower than those found by BeDell et al 21 and Szollar et al, 36 but do support the extent of bone loss at these sites in our SCI individuals.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Hip region BMD in our SCI group was 67, 66 and 63% that of the control group, for FN, WT and T, respectively. These ®gures are slightly lower than those found by BeDell et al 21 and Szollar et al, 36 but do support the extent of bone loss at these sites in our SCI individuals.…”
Section: Discussionsupporting
confidence: 74%
“…21 ± 23 However, results of load-bearing exercise in a microgravitational environment have been equivocal. 11,12,20,21,24,25 The purpose of this study was to compare bone mineral density of the total body, upper limbs, lower limbs, hip, and spine regions in a group of very active spinal cord injured adult males with values obtained in active able-bodied controls, carefully matched for age, height, and weight.…”
Section: Introductionmentioning
confidence: 99%
“…9,11 Reductions in hip region BMD were large, with the average femoral neck BMD being 74% that of agematched controls (LUNAR database). BeDell et al 29 (DEXA) found 79% BMD for the femoral neck in a group of paraplegics of similar duration of injury. This places our paraplegics in a high risk category for fracture.…”
Section: Discussionmentioning
confidence: 97%
“…[4][5][6][7] Clinical and experimental studies indicate that neuromuscular electrical stimulation can both affect and effect changes in muscle fibre contractile properties 4,8 and metabolism, 9,10 as well as responses at physiological 5,6 and functional levels. Although well studied, 7,[11][12][13] there is conflicting evidence about the efficacy of electrically evoked muscle activation in the stimulation of bone metabolism (bone formation and/or reduction of bone loss), and the clinical role of functional electrical stimulation (FES) in the treatment of osteoporosis resulting from neurological damage. The reason for this conflict may be that bone metabolic abnormalities may be time dependent [14][15][16] or as-yet-unexplained factors affect the osteogenic response to mechanical strain.…”
Section: Introductionmentioning
confidence: 99%